THE BASICS OF EDUCATING YOUNG PEOPLE IN THE SPIRIT OF PATRIOTISM IN SECONDARY SPECIAL EDUCATION - Jozilov Azamat Avazovich (Bright Mind Publishing, 2025)
This article provides information on the patriotic factors that attract young people to the military in secondary special military educational institutions. Today, the most important task of the state is to prepare young people for service in the Armed Forces of the Republic of Uzbekistan. It also aims to instill in young people patriotic ideas, to instill in their minds and thinking that the defense of the homeland is an honorable and sacred duty, and to arouse their interest in the military profession and a sense of pride in our national army.
Keywords: Spiritual courage, heritage, spiritual threat, enlightenment, morality, professional education.